2017
DOI: 10.15446/dyna.v84n203.65386
|View full text |Cite
|
Sign up to set email alerts
|

Estudio del comportamiento de variables para la integración del sistema de dirección de la empresa con enfoque de arquitectura empresarial

Abstract: Enterprise Architecture as Information Communication Technologies (ICTs) integration approach, and the theory of Integration of Management System in Enterprises(IMSE) have as common element the integration; however IMSE couldn´t develop capacities for ICTs integrated administration since management perspective, in a competitively business context marked for an efficient management of ICTs to achieve strategic goals. In this article is proposed an instrument for assessing interrelated variables of enterprise ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 10 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…This method has been applied to different Cuban enterprises obtaining good results and providing an effective mechanism to improve the IMSE [17]. This paper aims to strengthen the theoretical study from the observed data of the different considered companies.…”
Section: Fuzzy Decision Rules Analysismentioning
confidence: 97%
See 4 more Smart Citations
“…This method has been applied to different Cuban enterprises obtaining good results and providing an effective mechanism to improve the IMSE [17]. This paper aims to strengthen the theoretical study from the observed data of the different considered companies.…”
Section: Fuzzy Decision Rules Analysismentioning
confidence: 97%
“…Now, we will present the main variables of the EA we have detected, and the relations among them, which have been obtained from a study of the EA literature and prestigious EA experts [17,21]. As a consequence, diverse cause-effect relations, existing among the introduced EA variables, have been established.…”
Section: Design Of the Smea-imsementioning
confidence: 99%
See 3 more Smart Citations